Development of reduced graphene oxide from biowaste as an electrode material for vanadium redox flow battery - Abbas, Aumber (2022)
Vanadium redox flow battery (VRB) is a renowned electrochemical energy storage device for large scale applications owing to its promising storage capability, long life and safety. However, the lower efficiency of VRB system combined with the non-renewable graphite-based electrodes have limited the widespread of VRB commercial market. This study investigates the feasibility of converting renewable biomass waste, namely spent coffee beans, into reduced graphene oxide (rGO) as an alternate electrode material for VRB system. As prepared rGO has been thoroughly characterised and employed to design a modified electrode for VRB. The electrochemical performance of rGO based modified electrodes has been comprehensively examined using electrochemical impedance spectroscopy, cyclic voltammetry and galvanostatic charge-discharge cycling. The results demonstrate that the energy, voltage and coulombic efficiencies of rGO based electrodes are over 90%, which are comparable to that of commercially used pristine graphite electrode. Moreover, a stable cyclic performance is observed for rGO based electrodes over a total of 65 cycles owing to their high electrocatalytic activity and improved charge transfer. The stable performance and comparable efficiency present promising potential of biomass derived rGO as a low-cost replacement to the commercial graphite as an electrode material for VRB applications.